Estimates of heritability for several characters, in two soybean crosses - Destro, Deonísio; Sediyama, Tuneo; Silva, José Carlos; Sediyama, Carlos Sigueyuki; Thiébaut, José Tarcísio Lima (Pesquisa Agropecuaria Brasileira, 2014)
The F2 and F3 generations of Paraná x UFV-1 and IAC-2 x UFV-1 crosses were planted in Viçosa, Minas Gerais State, Brazil, respectively in the growing seasons of 1978/79 and 1979/80 and the F4 generation in Viçosa and Capinópolis, MG, in the growing season of 1980/81, in order to study the heritability of some agronomic characters of soybean (Glycine max (L.) Merrill). Significant and consistent heritability estimates were obtained for the studied reproductive stages, and the lowest values were obtained for seed production. The restricted sense F2 generation heritabilities, estimated by the regression of F3 lines, over F2 plants, expressed in real terms and standard deviation, were inferior when compared to F3 generation, estimated in the broad sense, based on plot data and to F4 generation, also evaluated in the broad sense, based on the plot means using the variance analysis component method. When the heritabilities estimated by the regression coeficient method (b) were high, the values obtained by the standard regression coeficient method (b') were relatively lower, showing the contrary when the heritabilities estimated by the first method was low.